1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

How does F = -KX become A = -KX

  1. Sep 15, 2009 #1
    1. The problem statement, all variables and given/known data

    how does F = -KX become A = -KX

    where A = -W^2 X

    A = acceleration
    x = displacement
    k = constant
    f = force
    2. Relevant equations



    3. The attempt at a solution
     
    Last edited: Sep 15, 2009
  2. jcsd
  3. Sep 15, 2009 #2

    rl.bhat

    User Avatar
    Homework Helper

    Explalin the symbols.
    What is A, W?
     
  4. Sep 15, 2009 #3
    I'm kinda lost here...if F = -kx and A = -kx, then F = A??
    Could you further clarify your question and perhaps provide some sort of a context?
     
Know someone interested in this topic? Share this thread via Reddit, Google+, Twitter, or Facebook